Investigating the prevalence of halitosis and its associated factors amongst the general population of Karachi, Pakistan - Warisha Tul Islam; Anisa Azhar; Tehniat Faraz Ahmed; Amynah Charania Shaikh (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the prevalence of halitosis among the general population of Karachi, and to identify factors contributing to its occurrence. Method: The cross-sectional study was conducted from March to July 2022 in Karachi after approval from the ethics review board of Dow University of Health Sciences, Karachi, and comprised the adult population of Karachi. Data was collected online using a questionnaire that was piloted before its link was distributed through social media platforms. The questionnaire evaluated the association of demographic features with self-perceived halitosis on the basis of which factors predictive of halitosis were determined. Data was analysed using SPSS 26. Results: Of a total of 342 subjects, 182(53%) were females and 160(47%) were males. There were 141(41) subjects aged 18-25 years, and 166(48%) were graduates. Overall, 240(70%) subjects reported to have self-perceived halitosis. Age, monthly household income, niswar and tea consumption, irregular use of dental floss and tongue cleaning were associated with higher incidence of halitosis (p<0.05). Carrying water bottle while outside was associated with decreased halitosis (p=0.007). Symptoms of gastroesophageal reflux disease, sinusitis, asthma, diabetes, hypertension and mental stress were associated with halitosis (p<0.05). Higher monthly household income and daily use of dental floss predicted lower odds of halitosis (p<0.05). Conclusion: Maintaining good oral hygiene and hydration reduced, while comorbid conditions increased the probability of halitosis. Key Words: Halitosis, Sinusitis, Gastroesophageal, Tongue, Hypertension, Asthma, Tea.